2022
DOI: 10.1093/ecco-jcc/jjab232.510
|View full text |Cite
|
Sign up to set email alerts
|

P383 Ustekinumab as an opportunity for refractory Ulcerative Colitis patients

Abstract: Background There are limited data in real-life of ustekinumab (USK) used in ulcerative colitis (UC). The aim of this study was to assess the effectiveness and safety in clinical practice of USK in UC in the medium and long-term. Methods Observational study in UC patients who received USK at the recommended dose based on weight ~6 mg/kg IV week, 0.90 mg SC week, 8 and maintenance, 90 mg SC every, 8 or, 12 weeks and with, 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In all, 11 studies [6][7][8][9]16,19,20,[22][23][24]26 Between-study heterogeneity was considerable at week 8 (I 2 = 87%) and month 12 (I 2 = 82%), might be not important at weeks 12-16 (I 2 = 26%), and was substantial at month 6 (I 2 = 65%) (Figure 1).…”
Section: Primary Endpoint: Clinical Remissionmentioning
confidence: 98%
See 4 more Smart Citations
“…In all, 11 studies [6][7][8][9]16,19,20,[22][23][24]26 Between-study heterogeneity was considerable at week 8 (I 2 = 87%) and month 12 (I 2 = 82%), might be not important at weeks 12-16 (I 2 = 26%), and was substantial at month 6 (I 2 = 65%) (Figure 1).…”
Section: Primary Endpoint: Clinical Remissionmentioning
confidence: 98%
“…Of the 254 citations identified, 19 studies including 3786 patients with UC were eligible for inclusion in this systematic review (Table S2). [5][6][7][8][9][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In all, 13 studies were reported as full-text articles, and 6 were conference proceedings. According to JBI criteria for quality assessment, 14 studies showed low risk of bias, and 5 articles showed moderate risk (Table S3).…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations